Analysis of China's fight against COVID-19 from the perspective of policy tools—policy capacity - Zhu, Shuicheng; Feng, Shuaiyao; Ning, Xiaoling; Zhou, Yiwei (Frontiers in Public Health, 2022)
Judging from the the number of confirmed cases, deaths, cures and the time taken to restore normal social and economic order, China is undoubtedly one of the most successful countries in fighting the Covid-19 pandemic, which highlights strong policy capacity of Chinese government using policy tools to solve policy problems efficiently. Based on the policy tools theory put forward by Roy Rothwell and Walter Zegveld, this paper analyzes the specific policy tools used in the prodromal period, breakout period, chronic period and resolution period of China's COVID-19 pandemic and further summarizes three characteristics. The characteristics are the comprehensive use of policy tools, staging of the use of policy tools in different periods and the dominant position of supply-oriented policy tools.